THE DEVELOPMENT DESIGN OF CURRICULUM 2013 FOR FIQIH LEARNING THROUGH A HUMANISTIC APPROACH - Monaziroh, Anika; Choirudin, Choirudin (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aims to describe the design of the 2013 curriculum development and the humanistic approach through the 2013 curriculum (Core Competencies and Basic Competencies) in Islamic jurisprudence subjects at Madrasah Ibtidaiyah (MI). The authors consider that it can later be the best solution for learning Fiqh through a humanistic approach. This research method uses content analysis. Content analysis is a research that is an in-depth discussion of the content of information contained in a mass media (analysis of the content of the object is mainly mass media). This study indicates several curriculum designs in 2013, including scientific discipline curriculum design, community-oriented curriculum design, student-oriented curriculum design, technological curriculum design, and Fiqh curriculum material. A balance must be reached between the materials that describe the principles of humanistic education. In this study, the authors also provide a solution that the concept of Fiqh learning uses a humanistic approach.Â